Comparative analysis of conventional and modified peak-detection based control technique for cascaded H-bridge multilevel inverter based shunt active power filter - Ray, Soumyadeep; Gupta, Nitin; Gupta, R. A. (2017 Innovations in Power and Advanced Computing Technologies (i-PACT), 2017)
This paper presents a modified peak-detection algorithm based control theory for three-phase, three-wire (3P-3W) Shunt Active Power Filter (SAPF) where Cascaded H-Bridge Multilevel Inverter (CHB-MLI) is used as a voltage source inverter (VSI) unit for reactive power compensation, power factor correction and harmonic mitigation in medium-voltage and high-power distribution system. The proposed control theory is implemented in MATLAB/Simulink platform and a rigorous comparative analysis is done with well known p-q theory and synchronous reference frame (SRF) theory to prove its effectiveness. Comparative study shows that modified control algorithm gives better transient performance in terms of settling time and peak overshoot.